Mandibular Fractures and Associated Factors at a Tertiary Care Hospital - Gadicherla, Srikanth (Arch Trauma Res, 2016)
OBJECTIVES: The aim of this study was to evaluate the distribution, etiology and type of mandibular fractures in subjects referred to our institution. METHODS: A retrospective study of 689 subjects, during the period from May 2010 to September 2013 with mandibular fractures was conducted. Information on age, gender, mechanism of injury and sites of trauma was obtained from the trauma registry. Data were tabulated and analyzed statistically. RESULTS: A total of 653 subjects had mandibular fractures, out of which 574 were males. The mean age of the participants was 31.54 ± 13.07. The majority of the subjects were between 21-40 years of age, in both males (61.7%) and females (54.4%). The major cause of fractures was road traffic accidents (87.4%) followed by fall (6.9%) and assault (4%), with the least frequent being gunshot injuries (0.3%). Almost half of the patients had parasymphysis fractures (50.2%), followed by angle (24.3%), condyle (20.4%), ramus (2.3%) and coronoid (2%). A total of 115 patients had bilateral fractures out of which 29 had parasymphysis, 12 had body fractures and 74 had bilateral condylar fractures. Double mandibular fractures were reported in 193 subjects; out of which 151 subjects had double contralateral and 42 had double unilateral fractures. Triple unilateral fracture was reported in only one subject. A total of 338 subjects had multiple fractures among the study population. CONCLUSIONS: Mandibular fractures can be complicated and demanding, and have a compelling impact on patients’ quality of life. Our study reported that parasymphysis was the most common region involved in mandible fractures.